(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Munif A, Nursalim M, Pradana AP. 2021. The potential of endophytic bacteria isolated from Tagetes sp. to control Meloidogyne spp. infection on tomato plants. Biodiversitas 22: 3229-3236. The root-knot nematode (Meloidogyne spp.) is one of the plant-parasitic nematodes that cause economical loss in the vegetable plantations in the world. The endophytic bacteria may act as a potential biological agent to control the plant-parasitic nematodes. The aim of this study was to explore the endophytic bacteria from Tagetes sp., which had a potential to control Meloidogyne spp. and act as growth promoter for tomato plants. The endophytic bacteria were isolated from the roots and stems of Tagetes sp. and tissues were cultured on the tryptic soy agar (TSA) media. The endophytic bacterial isolates were selected using hypersensitive and blood agar tests to identify their biological safety. The selected endophytic bacteria were also assessed for growth promoter test in the tomato plants. The selected endophytic bacteria were assessed in vitro against the Meloidogyne spp. juvenile 2 and their effectiveness in suppressing the root-knot nematodes on tomato plants in greenhouse. The results showed that total of 184 endophytic bacterial isolates were successfully isolated from the roots and stem of Tagetes sp. In hypersensitive and hemolytic tests, 78 and 36 isolates showed negative responses, respectively. Of the 36 isolates tested, it was found that 14 of them were able to promote the growth of tomato seedlings. In in vitro test, 14 endophytic bacteria showed 73-93% mortality rate of Meloidogyne spp J2. The results at greenhouse showed that 3 bacterial isolates, namely, AL21, AL44, and AL53 suppress the number of root-knot nematodes up to 50-74% and improve tomato plant growth by 32%. These results indicate that endophytic bacteria isolated from Tagetes sp. have the potential to act as biocontrol agents of parasitic nematodes and a plant growth promoter.